Innovation in urban healthcare : health kiosks - Maheshwari, Sunil Kumar; Ray, Prantika (London : Indian Institute of Management, Ahmedabad, 2018)
Urban Health is emerging new priority in the healthcare sector in India owing to unprecedented migration of people to urban areas and the rapid growth of urban populations. The growth of urban populations presents new health challenges due to the unhygienic conditions and lack of space for health facilities in urban slums. To address these challenges the government of Punjab set up Health Kiosks in slum areas to provide much needed medical services. The case invites the students to consider the effectiveness of the health kiosk program and if there are ways to make the program more sustainable.
Originally Published InMaheshwari, S. K., & Ray, P. (2018). Innovation in Urban Healthcare: Health Kiosks. CMHS0040. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Urban health -- India -- Punjab -- Case studies; Medical care -- India -- Punjab -- Case studies; Poor -- Medical care -- India -- Punjab -- Case studies